PENGEMBANGAN COOKIES DIBERLIN BERBAHAN DASAR TEPUNG BERAS HITAM DAN TEPUNG MOCAF DENGAN PENAMBAHAN INULIN DAN KACANG TANAH SEBAGAI ALTERNATIF SNACK BAGI PASIEN DIABETES MELLITUS - Munawar, Asep; Gumilar, Mulus; Fitria, Mona; Moviana, Yenny; Purba, Jedya Lucas A. (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
Diabetes Mellitus (DM) is a group of metabolic disorders characterized by chronic hyperglycemia (elevated blood glucose levels) resulting from impaired insulin secretion, insulin action, or both. Dietary management is one of the key components in diabetes care, including the selection of healthy snack options that are low glycemic index and high in dietary fiber. This study aimed to determine the effect of varying proportions of black rice flour and mocaf on the organoleptic properties of Diberlin Cookies, followed by an analysis of their nutritional composition and product cost. This experimental study involved 30 semi-trained panelists for organoleptic testing. The results showed that among the three formulations, there were significant differences in aroma, taste, texture, and overall acceptance with p-values < 0.05, whereas color showed no significant difference with a p-value > 0.05. Formula 3, with an average overall acceptance score of 6.13 (“Like”), was identified as the most preferred formulation. Proximate analysis indicated that the nutritional values (energy, carbohydrates, fat, and fiber) met the dietary requirements for diabetic-friendly snacks, although the protein content remained below the recommended standard. The estimated cost per serving of the best formulation (F3) was IDR 3,871.8. To improve protein content, it is recommended to modify the formulation by incorporating high-protein ingredients such as mung bean flour or other legume-based flours.